Long-term trends in child maltreatment in England and Wales, 1858–2016: an observational, time-series analysis. (March 2019) - Degli Esposti, Michelle; Humphreys, David K; Jenkins, Benjamin M; Gasparrini, Antonio; Pooley, Siân; Eisner, Manuel; Bowes, Lucy
Summary: Background: It is unclear whether child maltreatment is increasing or decreasing in England and Wales. More evidence is needed, from multiple sources and over longer periods of time, to explore trends in child maltreatment. We investigated whether the annual incidence of child maltreatment has changed over time, using official record data and time-series methods to establish long-term trends. Methods: In this observational time-series analysis, we used six data sources (Government records for child mortality, police-recorded child homicides, crimes against children, child protection, and children in care; and NSPCC data) to estimate the incidence of child maltreatment in England and Wales and examine long-term trends. We included nationally representative data that could estimate the incidence of child maltreatment for more than 25 years. Our primary outcomes were the number of victims (age <20 years) or perpetrators (age >16 years) of child maltreatment per 12-month period in England, including or excluding Wales. We fitted Poisson regression models with year as the exposure and the number of victims or perpetrators of child maltreatment as the outcome (adjusted for population age-structure and size). When a linear trend was not appropriate, we fitted generalised additive models with penalised splines to visualise trends. Findings: The incidence of child mortality by homicide or assault decreased by 90% (2·7 per 100 000 children) between 1858 and 2016 and the incidence of people guilty of child cruelty or neglect decreased by 83% (6·7 per 100 000 adults) between 1893 and 2016, whereas child protection registrations increased by 182% (328·7 per 100 000 children) between 1988 and 2016. Crimes against children and children entering care increased between 2000 and 2016. In 2016, 40 children died by homicide, with twice as many adolescent (15–19 years) deaths than infant (age <1 year) deaths. In 2016, 67 700 children were placed on the child protection register and neglect and emotional abuse were the most common reasons. Interpretation: Although long-term trends have decreased, child maltreatment remains a major public health problem in England and Wales. Further research is needed to establish whether adolescents are a particularly vulnerable age group and whether neglect and emotional abuse are increasing. Future child protection policies and practices should respond to these areas of growing need. Funding: Andrew W Mellon Foundation and Clarendon through The Oxford Research Centre in the Humanities, Oxford.